Fiscal and Monetary Policy Tools for Green Economy Development in Nepal - Shrestha, Jamuna; Adhikari, Gyan Mani; Aryal, Jitendra (Journal of Development and Administrative Studies, 2025)
Nepal faces major environmental challenges, including climatic vulnerability, deforestation, and unsustainable resource consumption, yet the country contributes only 0.027% to global greenhouse gas emissions. The country is a very climate-vulnerable country in the world, but the monetary and fiscal policy tools of green economy development are underdeveloped. This paper analyzes how fiscal and monetary policy instruments can help develop a green economy in Nepal, identifies gaps in policy, and proposes a comprehensive sustainability transition framework. The study uses qualitative research design, which will incorporate systematical document analysis of 15 major government policies and regulatory frameworks, comparative case study analysis of eight countries that have established green economy policies (Bhutan, Costa Rica, India, Bangladesh, China, Sweden, Norway, and Thailand), and secondary data analysis based on government statistical reports and international databases with a period of 2015 to 2023. Green finance is only 5.35% of banking sector credit, and the environmental fiscal revenues in the country are only 1.24% of the total government revenue, still well below other global standards of 3–6 times higher. According to a multi-criteria evaluation, green refinancing facilities (7.8/10), green bonds (7.3/10), and payment of ecosystem services (7.3/10) are the priority instruments. The policy package suggested has a payoff-to-cost ratio of 7:1, forecasting a 234:272 percentage growth in green investment, 140,000-180,000 new green jobs, and a payoff of a 14-18 percent decline in CO 2 emissions within a period of five years. The strategic use of integrated fiscal and monetary policies can help Nepal move towards sustainable development faster. However, its successful implementation must be based on institutional capacity building, a staged implementation with the introduction of green refinancing facilities first, coordination of stakeholders, and adjustable governance systems that suit the specific socio-economic situation in Nepal.